Designing an independent panel on evidence for action on antimicrobial resistance: Lessons from selected bodies in global health, climate change and biodiversity - Viviana Munoz Tellez; Francesca Chiara (South Centre, 2025)
This paper proposes a framework for designing an Independent Panel on Evidence for Action on Antimicrobial Resistance (IPEA), responding to the 2025 United Nations General Assembly mandate. Through a comparative analysis of selected international scientific advisory bodies, we identify the panel's mandate as the foundational element that will critically shape its composition, scope, deliverables, and governance structure. Our framework addresses key domains of credibility, scientific integrity, authority, policy relevance, and sustainability while establishing equity as a fundamental design principle - not merely ensuring low and middle-income country (LMIC) participation but designing the IPEA to address existing imbalances in antimicrobial resistance (AMR) evidence production and dissemination. We analyse potential mandate options, from evidence synthesis to policy recommendations, highlighting the importance of defining a unique and complementary role for IPEA within the existing AMR governance landscape to avoid duplication and maximize impact on global AMR response.
Keywords: 300; Antimicrobial Resistance (AMR); Biodiversity; Climate Change; Global Health; Health; Independent Panel on Evidence for Action against AMR; Low- and Middle-income Countries (LMICs)